Synopsis of the antlion genus Deutoleon Navás, 1927 in China (Neuroptera: Myrmeleontidae) - Zhan, Qingbin; Li, Sha; Wang, Xinli (Zootaxa, 2012)
A synopsis of the genus Deutoleon Navás, 1927 (Neuroptera: Myrmeleontidae) is presented. The little known species Deuto-leon turanicus Navás, 1927 is newly recorded from China. Two species of Deutoleon are redescribed and illustrated in detail, including the female of D. turanicus. A key to species of Deutoleon is provided.